O datowaniu emisji triumviri monetales z lat 13-12 p.n.e. - Jegliński, Adam (Acta Universitatis Lodziensis. Folia Archaeologica, 2004)
The author's intention is to take an attitude towards the proposal of dating the coins struck during the reign of Augustus in a mint in Rome that were signed by triumviri monetales. The coins have been prosented by an eminent Polish numismatist A. Kunisz in Researches sur le monnayage et la circulation monetaire sous le régne ď August. Most of the suggestions included in the work are convincing. However, some of the proposals on the dating of the triumviri monetales coins from the years 13-12 B.C., raise serious doubts. Besides, it is not intended to question the absolute dating but the way of matching the emissions of each triumviri to the years 13 and 12 B.C. According to A. Kunisz in 13 B.C. the triumviri monetales functions were performed by the college of L. Caninius Gallus, L. Lentulus, C. M. Tromentina, in 12 B.C. the college consisted of Cossus Lentulus, S. C. Platorinus, C. Antistius Reginus. In the years of our interest three very important events took place. In 13 B.C. Augustus and Agrippa came to tribune power and imperium maius for five years. Next year on March 12th Agrippa died and Augustus, after Lepidus death, achieved a status of the Pontifex Maximus. Therefore the coins struck in 12 B.C. could refer to acquiring a status of the tribune and Pontifex Maximus by Agrippa, while those struck in the previous year could only be a hint of conferring the tribune power and imperium maius (the death of Lepidus could not have been foreseen). Some denarii of C. Antistius Reginus and Caninius Gallus refer to election of Augustus of the Pontifex Maximus (nos 1, 2, 3). An inscription C. (OMITIA) C. (AESARIS) AUGUSTI on the denarii (no 2) of Caninius Gallus cannot refer to conferring a status of tribinitia potestas on Augustus because it was granted by the senate and comitia only accepted it. Besides, why could Agrippa passed over, a person who was promoted on coins by propaganda and who together with Augustus achieved tribunitia potestas and imperium maius. Whereas the Pontifex Maximus was chosen by the comitia in accordance with tradition. Therefore the coins of Caninius Gallus must come not from 13 B.C. but from 12 B.C. On the coins signed by Cossus Lentulus and Sulpicius Platorinus there is no reference to the Pontifex Maximus election, but the following are depictured: bust of Agrippa wearing corona muralisi and rostralis as well as a tandem Augustus - Agrippa sitting on bisellium (no 5). The main issue is conferring imperium maius on Augustus and Agrippa. A. Kunisz dated the coins of Cossus Lentulus to 12 B.C. justifying it by Agrippa’s horse statue image on it (no 6), which was intended to be an allusion to his after-death heroization. The rider on the coins is not halfnaked and there is no clear indication in favour of Agrippa’s after-death heroization, therefore the coins of the triumviri mentioned above should be dated to 13 B.C. Images on the coins of M. Tromentina do not give unambiguous indication. However, if we interpret an image of an empty quadriga with a palm branch as an allusion to Augustus’ refusal of a triumph acknowledged for his victories on the East, the coins should also be dated to 13 B.C. Denarii of L. Lentulus (no 8) present Augustus with clipeus virtutis while placing a star above a half-naked figure standing next to him. It is supposed that this is Julius Caesar, above whose head either Octavian or Agrippa is placing the Julius star. The latter seems to be more probable because Agrippa was not officially acknowledged divinity, but a splendid form of the funeral, burial in Augustus Mausoleum, some relics (probably the Belvedere altar) and his clear presence on the coins in his last years of life can testify his strong position and suggest his informal heroization of Augustus’ will. That can be dymbolised by the image of Augustus holding a star above Agrippa’s head on the coins of L. Lentulus. The star is not only Caesar’s attribute. Star of this type later appears above Germanicus’ image (relief from Ravenna), and in the 1st half of the 2nd century A.D. on a grave relief above a head of a few years’ slave (no 9). It would have been strange to honour Caesar in such a way just in 13 B.C. since Octavian’s propaganda had not used this motif even during a struggle for succession after assassinated Cesar. Augustus is placed higher then his protagonist and himself is holding a star above his head. Such gestures rise Augustus and seem to be more adequate to Agrippa than to Caesar. According to what have been said above, the coins refer to Agrippa’s death so they must have been emitted in 12 B.C. One of the main arguments of A. Kunisz’s chronology is that since 12 B.C., displaying of monetary busts of Augustus wearing a laurel wreath became a rule, as it was in Lugdunum, but it does not have confirmation in calculations. In 12 B.C., coins with Augustus’ bust and with a laurel wreath were not struck, they appeared in the following year, but the year 12 B.C., did not stand out against the background of the triumviri monetales coinage among which types of coins with a bust withoud a wreath prevail. It can be explained by the fact that Augustus’ power in Italy was of civilian and in Gallia of military character; yet a wreath is an attribute of a victorious commander.